2022
DOI: 10.1088/1572-9494/ac6fc2
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic and valley-resolved beam-splitter based on a tilted Dirac system

Abstract: We investigate theoretically valley-resolved lateral shift of electrons traversing a n-p-n junction bulit on a typical tilted Dirac system (8-Pmmn borophene). A gauge-invariant formula on Goos-Hanchen (GH) shift of transmitted beams is derived, which holds for any anisotropic isoenergy surface. The tilt term brings valley dependence of relative position between isoenergy surface in n region and that in p region. Consequently, valley double refraction can occur at the n-p interface. The exiting positions of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…6 For a typical tilted Dirac system (8-Pmmn borophene), the valley-resolved lateral shift of electrons traversing an n-pn junction was studied theoretically. [101] We derive a gaugeinvariant formula on the GH shift of transmitted beams, which holds for any anisotropic isoenergy surface. Due to the similarity between the tilting effect of the Dirac cone and straininduced vector potential in graphene, valley double refraction also occurs at the considered n-p interface.…”
Section: Goos-hänchen Shift In Strained Graphenementioning
confidence: 99%
“…6 For a typical tilted Dirac system (8-Pmmn borophene), the valley-resolved lateral shift of electrons traversing an n-pn junction was studied theoretically. [101] We derive a gaugeinvariant formula on the GH shift of transmitted beams, which holds for any anisotropic isoenergy surface. Due to the similarity between the tilting effect of the Dirac cone and straininduced vector potential in graphene, valley double refraction also occurs at the considered n-p interface.…”
Section: Goos-hänchen Shift In Strained Graphenementioning
confidence: 99%
“…It supplies more opportunities in valleytronics. Recently, valley-contrasting Goos-Hänchen shift, gate-tunable valley filtering, and valley-resolved beam-splitter have been found in the tilted Dirac system [26][27][28]. With attention to the valley dependent device applications, there is reason to believe that 8-Pmmn borophene will provide a good material platform, and show significant advantages in some respects comparing with graphene.…”
Section: Introductionmentioning
confidence: 99%
“…In 2D materials based-systems, the spintronic properties can be controlled by the Rashba interaction, which can be adjusted by an external electric field [25]. The transport properties in the structures based on the 8-Pmmn borophene have been extensively investigated over the recent years [26][27][28][29][30][31][32][33][34][35][36][37]. The anomalous heat transport through 8-Pmmn borophene sheet has been studied by Sengupta et al [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that, Goos-Hänchen-like shift in this structures has a strong dependence on the direction of the junctions. Anisotropic transmission and valleydependent transport properties through 8-Pmmn borophenebased n-p-n junction have been investigated theoretically by Zhou et al in [36]. It is demonstrate that, valley-polarization current depends on the incident electron angle and energy of the incident electron as well as junction parameters.…”
Section: Introductionmentioning
confidence: 99%